A CD4+CD161+ T-Cell Subset Present in Unexposed Humans, Not Tb Patients, Are Fast Acting Cells That Inhibit the Growth of Intracellular Mycobacteria Involving CD161 Pathway, Perforin, and IFN-γ/Autophagy - Yang, Rui; Peng, Ying; Pi, Jiang; Liu, Yidian; Yang, Enzhuo; Shen, Xiaona; Yao, Lan; Shen, Ling; Modlin, Robert L.; Shen, Hongbo; Sha, Wei; Chen, Zheng W. (Frontiers in Immunology, 2021)
It remains undefined whether a subset of CD4+ T cells can function as fast-acting cells to control Mycobacterium tuberculosis (Mtb) infection. Here we show that the primary CD4+CD161+ T-cell subset, not CD4+CD161-, in unexposed healthy humans fast acted as unconventional T cells capable of inhibiting intracellular Mtb and BCG growth upon exposure to infected autologous and allogeneic macrophages or lung epithelial A549 cells. Such inhibition coincided with the ability of primary CD4+CD161+ T cells to rapidly express/secrete anti-TB cytokines including IFN-γ, TNF-α, IL-17 and perforin upon exposure to Mtb. Mechanistically, blockades of CD161 pathway, perforin or IFN-γ by blocking mAbs abrogated the ability of CD4+CD161+ T cells to inhibit intracellular mycobacterial growth. Pre-treatment of infected macrophages with inhibitors of autophagy also blocked the CD4+CD161+ T cell-mediated growth inhibition of mycobacteria. Furthermore, adoptive transfer of human CD4+CD161+ T cells conferred protective immunity against mycobacterial infection in SCID mice. Surprisingly, CD4+CD161+ T cells in TB patients exhibited a loss or reduction of their capabilities to produce perforin/IFN-γ and to inhibit intracellular growth of mycobacteria in infected macrophages. These immune dysfunctions were consistent with PD1/Tim3 up-regulation on CD4+CD161+ T cells in active tuberculosis patients, and the blockade of PD1/Tim3 on this subset cells enhanced the inhibition of intracellular mycobacteria survival. Thus, these findings suggest that a fast-acting primary CD4+CD161+T-cell subset in unexposed humans employs the CD161 pathway, perforin, and IFN-γ/autophagy to inhibit the growth of intracellular mycobacteria, thereby distinguishing them from the slow adaptive responses of conventional CD4+ T cells. The presence of fast-acting CD4+CD161+ T-cell that inhibit mycobacterial growth in unexposed humans but not TB patients also implicates the role of these cells in protective immunity against initial Mtb infection.